Local factors and innovativeness: an empirical analysis of German patents for five industries - Tom Broekel; Thomas Brenner (Max Planck Institute of Economics, 2005)
A growing body of work emphasizes the role that the spatial component plays in the in the innovation process. These perspectives brought the region's infrastructure and its endowment with crucial factors into the focus of research. Given that these factors do significantly influence the innovativeness of local firms, it is important to identify precisely which regional characteristics matter. The aim of this paper is to identify a number of key influences out of a multitude of structural factors that are thought to influence the firm's innovation activity. We examine more than eighty variables that approximate the financial, geographical and social-economic factor endowment of a region. The variables are tested with a linear and log - linear model. The two staged procedure examines the variable's bivariate correlation with patent data of five industries. Based on these outcomes multivariate regression models are applied in the second stage. The results for the different models are compared and their advantages and disadvantages are discussed. We find a strong impact of economic agglomeration, extramural science institutions and human capital. In the case of human capital, especially the graduates at the technical colleges are collocated with high regional innovativeness. Furthermore, significant differences are observed for the five industries and for using the two models.
Keywords: 330